Detection of mRNAs for macrophage products in inflammatory bowel disease by in situ hybridisation. Issue 9 (September 1992) - Cappello, M; Keshav, S; Prince, C; Jewell, D P; Gordon, S
Abstract : In situ hybridisation has been used to detect mRNAs to the macrophage secretory products, lysozyme, interleukin 1 beta and tumour necrosis factor-alpha. Sections of paraformaldehyde fixed, frozen colonoscopic biopsies from patients with ulcerative colitis, Crohn's disease or normal controls were hybridised with specific radiolabelled probes and the signal detected by autoradiography. Lysozyme mRNA expression was more common in ulcerative colitis (22/27) and Crohn's disease (eight of eight) compared with controls (17/27). Positive cells were found mainly in the subepithelial region in normal colon, while in inflammatory bowel disease they also appeared in the deeper lamina propria. Immunocytochemistry in parallel sections showed that lysozyme mRNA was expressed only in macrophages or in metaplastic Paneth cells in longstanding inflammatory bowel disease. Tissue neutrophils did not express the lysozyme mRNA, though they have large stores of the protein. Tumour necrosis factor mRNA was detected in four of nine controls compared with 11/15 inflammatory bowel disease patients. For interleukin 1 beta, three of eight controls were positive compared with 10/13 with ulcerative colitis. The tumour necrosis factor signal was located mainly in the deeper lamina propria whereas the interleukin 1 beta was seen in subepithelial macrophages. These results confirm increased macrophage activation in inflammatory bowel disease and suggest functional heterogeneity within the intestinal macrophage population.